PEMBATASAN TERHADAP HAK ASASI MANUSIA DALAM PRESPEKTIF KEADAAN DARURAT - Matompo, Osgar S (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
HumanÂ rightsÂ is a giftÂ from Allah SWT, as a consequence becoming humanÂ creature, thereforeÂ it couldnât be deprivedÂ orÂ abolishedÂ byÂ theÂ state.Â IfÂ aÂ stateÂ inÂ anÂ abnormalÂ conditionÂ orÂ emergencyÂ condition,Â stateÂ is allowedÂ toÂ take an extraordinary actionÂ including giving restrictionÂ to humanÂ rightÂ forÂ theÂ sake of defending stateÂ integrityÂ andÂ protectÂ itsÂ citizens, butÂ humanÂ rightÂ thatÂ couldÂ beÂ restrictedÂ isÂ humanÂ right whichÂ is categorizedÂ inÂ non-derogableÂ rightÂ (rightÂ thatÂ couldnâtÂ beÂ limitedÂ inÂ anyÂ kind ofÂ condition).Â ThisÂ research foundÂ thatÂ inÂ the practice of humanÂ right restriction whichÂ is appliedÂ in any kind of emergency conditionÂ in various area ofÂ Indonesia preciselyÂ touchÂ theÂ rights which are non-derogableÂ rights.